Pathways disrupted in human ALS motor neurons identified through genetic correction of mutant SOD1 - Kiskinis, Evangelos; Sandoe, Jackson; Williams, Luis A; Boulting, Gabriella L; Moccia, Rob; Wainger, Brian J; Han, Steve; Peng, Theodore; Thams, Sebastian; Mikkilineni, Shravani; Mellin, Cassidy; Merkle, Florian T; et al. (Cell stem cell, 2014)
Although many distinct mutations in a variety of genes are known to cause Amyotrophic Lateral Sclerosis (ALS), it remains poorly understood how they selectively impact motor neuron biology and whether they converge on common pathways to cause neuronal degeneration. Here, we have combined reprogramming and stem cell differentiation approaches with genome engineering and RNA sequencing to define the transcriptional and functional changes that are induced in human motor neurons by mutant SOD1. Mutant SOD1 protein induced a transcriptional signature indicative of increased oxidative stress, reduced mitochondrial function, altered subcellular transport, and activation of the ER stress and unfolded protein response pathways. Functional studies demonstrated that these pathways were perturbed in a manner dependent on the SOD1 mutation. Finally, interrogation of stem-cell-derived motor neurons produced from ALS patients harboring a repeat expansion in C9orf72 indicates that at least a subset of these changes are more broadly conserved in ALS.